The Importance of Country-of-Origin Construct Dimensions in Destination Brand Building - Zoran Krupka; Mateja Mirt; Đurđana Ozretić Došen (Tržište, 2021)
Purpose – The primary purpose of this paper is to analyze the relationship between the country-of-origin (COO) construct and destination brand building (DBB) to reveal whether the COO construct and its dimensions are important for DBB. More specifically, the paper explores whether COO construct dimensions can impact destination branding. Design/Methodology/Approach – The research was conducted using a self-administered questionnaire on a sample of 409 respondents from the United States and Croatia. SPSS was used for data analysis. Findings and implications – While the COO is relevant for DBB, it cannot be used in the same manner as in product/service branding. Certain COO dimensions which are extremely important for product/service brands (e.g., level of technological development, standard of living) are not as critical for DBB. The political situation and perceived safety are COO dimensions that have proven to be important in the context of DBB. Limitations – The main limitation of the paper arises from sampling, relying on Facebook and LinkedIn for questionnaire distribution. Originality – With this research, we are decomposing the COO construct and investigating the impact of its dimensions on DBB.